2015
DOI: 10.1016/j.tetlet.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of pro-resolving and tissue-regenerative Protectin sulfido-conjugates

Abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Binding of glutathione at C16 of 17H(p)DHA produces protectin conjugated in tissue regeneration 1 (PCTR1, 16 R -glutathionyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) that is converted into PCRT2 (16 R -cysteinylglycinyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) and PCRT3 (16 R -cysteinyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) (Rodriguez and Spur, 2015b; Ramon et al., 2016). In addition to the name giving tissue regenerative actions, PCTRs possess immune-regulatory actions on innate lymphoid cells during bacterial infection in vivo (Dalli et al., 2017).…”
Section: Biosynthesis Of Spmmentioning
confidence: 99%
“…Binding of glutathione at C16 of 17H(p)DHA produces protectin conjugated in tissue regeneration 1 (PCTR1, 16 R -glutathionyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) that is converted into PCRT2 (16 R -cysteinylglycinyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) and PCRT3 (16 R -cysteinyl-4 Z ,7 Z ,10 Z ,12 E ,14 E ,16 R ,17 S ,19 Z -DHA) (Rodriguez and Spur, 2015b; Ramon et al., 2016). In addition to the name giving tissue regenerative actions, PCTRs possess immune-regulatory actions on innate lymphoid cells during bacterial infection in vivo (Dalli et al., 2017).…”
Section: Biosynthesis Of Spmmentioning
confidence: 99%
“…3 , 4 ), with the full 1 H-NMR spectra summarized in supplemental Tables S1 and S2 . These data directly establish the structures of these 15-LOX-1-derived epoxides: 14,15-LTA 5 as 14 S ,15 S - trans -epoxy-5 Z ,8 Z ,10 E ,12 E ,17 Z -EPA, and 16,17-DTA 6 as 16 S ,17 S - trans -epoxy-4 Z ,7 Z ,10 Z ,12 E ,14 E ,19 Z -DHA, with the data for the latter in accord with the synthetic epoxide ( 13 , 14 ).
Fig.
…”
Section: Resultsmentioning
confidence: 60%
“…Notwithstanding the technical challenges, leukotriene A4 (LTA 4 ) itself has been isolated from leukocyte incubations ( 11 ), and later, we prepared LTA 4 and its 5,6- cis -epoxide analogue using recombinant 5-LOX enzyme ( 12 ). Herein, we applied the methodology using recombinant human 15-LOX-1 to preparation of the LTA-related epoxides from n -6 hydroperoxides of EPA and DHA, the latter and 22:5ω3 analogue also prepared by total chemical synthesis ( 13 , 14 , 15 , 16 ).…”
mentioning
confidence: 99%
“…A new family of mediators in tissue regeneration, namely specialized proresolving mediator sulfido-conjugates (SPM-SCs), were recently discovered, and their stereochemical structures have been established. [10][11][12][13][14][15] These chemical mediator pathways give rise to unique bioactive structures that include maresin conjugates in tissue regeneration (MCTRs; Fig 1, A), protectin conjugates in tissue regeneration (PCTRs), and resolvin conjugates in tissue regeneration. [10][11][12]16,17 Of interest, recent results showed that MCTRs compete with LTD 4 binding on recombinant CysLT1, 18 thus warranting their investigation in mammalian tissues.…”
Section: Abstract: Resolution Inflammation Lung Asthmamentioning
confidence: 99%
“…A Poroshell 120 EC-18 column (100 mm 3 4.6 mm 3 2.7 mm; Agilent Technologies, Santa Clara, Calif) was kept in a column oven maintained at 508C, and materials were eluted in a gradient of methanol/water/acetic acid from 55:45:0.01 (vol/vol/ vol) to 98:2:0.01 at 0.5 mL/min flow rate. The second system, methanol fractions from SPE containing CysLTs and SPM-SCs, was identified and profiled 11,14 Technologies) was kept in a column oven maintained at 508C, and LMs were eluted in a gradient of methanol/water/acetic acid from 55:45:0.1 (vol/vol/ vol) to 98:2:0.1 at 0.6 mL/min flow rate. Multiple reaction monitoring was used with MS/MS matching signature ion fragments for each molecule (at least 6 diagnostic ions; approximately 0.1-pg limit of detection) and standard curves (r 2 > 0.98 for each LM and pathway marker) for both systems to monitor and quantify the levels of targeted LMs.…”
Section: Lc-ms/ms-based Metabololipidomics Of Human and Murine Lung Tmentioning
confidence: 99%